2021
DOI: 10.1021/acsami.1c09992
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Artificial Enzyme Activities on the Reconstructed Sawtoothlike Nanofacets of Pure and Pr-Doped Ceria Nanocubes

Abstract: In this work, a simple one-step thermal oxidation process was established to achieve a significant surface increase in {110} and {111} nanofacets on well-defined, pure and Pr-doped, ceria nanocubes. More importantly, without changing most of the bulk properties, this treatment leads to a remarkable boost of their enzymatic activities: from the oxidant (oxidase-like) to antioxidant (hydroxyl radical scavenging) as well as the paraoxon degradation (phosphatase-like) activities. Such performance improvement might… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 68 publications
0
6
0
Order By: Relevance
“…It can be noticed that materials shown in Table 2 exhibit an indirect bandgap smaller than the direct band gap, suggesting that the fundamental bandgap for these materials could be considered as an indirect bandgap [ 44 , 45 ]. The direct or indirect nature of the bandgap transition is an essential parameter of semiconductors for photocatalytic applications.…”
Section: Resultsmentioning
confidence: 99%
“…It can be noticed that materials shown in Table 2 exhibit an indirect bandgap smaller than the direct band gap, suggesting that the fundamental bandgap for these materials could be considered as an indirect bandgap [ 44 , 45 ]. The direct or indirect nature of the bandgap transition is an essential parameter of semiconductors for photocatalytic applications.…”
Section: Resultsmentioning
confidence: 99%
“…15,16 However, the catalytic activities of bare ceria are still moderate. Till now, numerous strategies have been developed to modulate the activities of nanoceria such as surface modification, 17,18 doping transition metals [19][20][21][22][23] and regulating morphology and size. 24,25 Zhao found that fluoride-capped nanoceria can significantly improve the oxidase-like activity of nanoceria, which stemmed from the increase of the concentration of Ce 3+ and the accompanying oxygen vacancies upon adding F À .…”
Section: Introductionmentioning
confidence: 99%
“…Ceria can exist in dual oxidation states as Ce 3+ and Ce 4+ , enabling the ability to accommodate a high density of oxygen vacancies (Vo), which enhances the catalytic activity for OPD due to the cooperative redox property of Ce 3+ and Ce 4+ [1,6,9,11] . The addition of metal dopants to ceria has shown to improve Vo concentration and associated catalytic activity for the decomposition of OPs [1,12–15] …”
Section: Introductionmentioning
confidence: 99%
“…[1,6,9,11] The addition of metal dopants to ceria has shown to improve Vo concentration and associated catalytic activity for the decomposition of OPs. [1,[12][13][14][15] Various approaches can be applied to synthesize oxide nanocatalysts to tune structure and thus catalytic properties; however, the majority of preparation methods exhibit common drawbacks, such as complicated synthetic procedures and/or energy intensive processes. [6,[16][17][18][19] To alleviate these concerns, benign biomineralization-based methods have received increased attention as a straightforward and efficient synthesis approach for metal oxide catalysts.…”
Section: Introductionmentioning
confidence: 99%